Mechanical and Pharmacological Revascularization Strategies for Prevention of Microvascular Dysfunction in ST-Segment Elevation Myocardial Infarction: Analysis from Index of Microcirculatory Resistance Registry Data - Ji-Hun Jang; Man-Jong Lee; Kyu-Yong Ko; Jin-Hee Park; Yong-Soo Baek; Kwon Sung-Woo; Sung-Hee Shin; Seong-Ill Woo; Dae-Hyeok Kim; Young Ju Suh; Jun Kwan; Sang-Don Park (Journal of Interventional Cardiology)
Objectives. We aimed to identify mechanical and pharmacological revascularization strategies correlated with the index of microcirculatory resistance (IMR) in ST-elevation myocardial infarction (STEMI) patients. Background. Microvascular dysfunction (MVD) after STEMI is correlated with infarct size and poor long-term prognosis, and the IMR is a useful analytical method for the quantitative assessment of MVD. However, therapeutic strategies that can reliably reduce MVD remain uncertain. Methods. Patients with STEMI who underwent primary percutaneous coronary intervention (PCI) were enrolled. The IMR was measured with a pressure sensor/thermistor-tipped guidewire immediately after primary PCI. High IMR was defined as values ≥66th percentile of IMR in enrolled patients (IMR > 30.9 IU). Results. A total of 160 STEMI patients were analyzed (high IMR = 54 patients). Clinical factors for Killip class P=0.006, delayed hospitalization from symptom onset P=0.004, peak troponin-I level P=0.042, and multivessel disease P=0.003 were associated with high IMR. Achieving final thrombolysis in myocardial infarction myocardial perfusion grade 3 tended to be associated with low IMR P=0.119, whereas the presence of distal embolization was significantly associated with high IMR P=0.034. In terms of therapeutic strategies that involved adjusting clinical and angiographic factors associated with IMR, preloading of third-generation P2Y12 inhibitors correlated with reducing IMR value (β = −10.30, P<0.001). Mechanical therapeutic strategies including stent diameter/length, preballoon dilatation, direct stenting, and thrombectomy were not associated with low IMR value (all P>0.05), and postballoon dilatation was associated with high IMR (β = 8.30, P=0.020). Conclusions. In our study, mechanical strategies were suboptimal in achieving myocardial salvage. Preloading of third-generation P2Y12 inhibitors revealed decreased IMR value, indicative of MVD prevention.